Strategi Kelompok Buruh Perempuan dalam Memanfaatkan Modal Sosial untuk Meningkatkan Aksesibilitas Pasar (Studi di Kelompok Buruh Perempuan “Tani Rejo” dalam Mengakses Industri Emping Melinjo di Kecamatan Limpung, Kabupaten Batang, Provinsi Jawa Tengah) - Jemadi Jemadi; Bambang Sugeng Dwiyanto (Universitas Proklamasi 45 Yogyakarta, 2014)
This paper discusses (1) power relation pattern between emping maker labor and employer in managing emping mlinjo industry, (2) female group “Tani Rejo” as female labor association in internal affair or in relation to external actor, and (3) implication occurring due to emerging female labor association. The paper is based on research done on female labor of emping industry in Ngaliyan village, Limpung district, Batang regency, Central Java province. Result of the research indicates that (1) women associated in Tani Rejo group leave from social construction binding them for long time. They use it as economic and sociological association. (2) by joining in Tani Rejo group, female labor get welfare benefit in material and non material aspects and democracy, polity education and other supporting insight that is very useful in social setting and household. (3) From activities the group does indicate that negotiation strategy is social tradition transformation to economic area. The social tradition is social capital the female labors have. Social capital is transformed into formal organization. Then, the organization does economic activities using social capital. (4) Existence of Tani Rejo as social modal did not give significant implication in relation between labor and employers, because Tani Rejo emerge as new actor that is still weak in human resource and capital resource.